2021
DOI: 10.1021/acs.jced.0c01073
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement of Crystal Form II and Form V Ticagrelor in Several Pure Organic Solvents

Abstract: Ticagrelor (TCG) is a P2Y12 platelet inhibitor and has several crystal forms including Form II and Form V. In this work, it has been confirmed that Form II TCG would gradually transform to Form V in selected solvents. According to the crystal form stability, a dynamic method was adopted to measure the solubility of Form II TCG in six pure solvents (n-propanol, isopropanol, n-butanol, 2-butanol, ethyl acetate, and isopropyl acetate). The solubility of Form V TCG in 12 pure solvents (methanol, ethanol, n-propano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In order to accurately determine the solid–liquid equilibrium point, EasyViewer was introduced to monitor the dissolution process. A similar experimental apparatus has been reported in our previous work . The high-resolution images caught by EasyViewer were analyzed by iC Vision 8.0.31 software to provide more information about suspension particles, such as turbidity and particle morphology.…”
Section: Solubility Measurement Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to accurately determine the solid–liquid equilibrium point, EasyViewer was introduced to monitor the dissolution process. A similar experimental apparatus has been reported in our previous work . The high-resolution images caught by EasyViewer were analyzed by iC Vision 8.0.31 software to provide more information about suspension particles, such as turbidity and particle morphology.…”
Section: Solubility Measurement Experimentsmentioning
confidence: 99%
“…A similar experimental apparatus has been reported in our previous work. 12 The high-resolution images caught by EasyViewer were analyzed by iC Vision 8.0.31 software to provide more information about suspension particles, such as turbidity and particle morphology. The experiment apparatus is shown in Figure 4.…”
Section: Solubility Measurementmentioning
confidence: 99%
“…The solubility of SH, Form I, and Form II in different aqueous ethanol at 60 °C was measured, as shown in Figure 25. [11] It was found that with the decrease of ethanol content, the solubility difference between SH and Form I increased, which meant that the driving force of the transformation expended, so the transformation was accelerated. It followed the general law of SMT.…”
Section: Transformation Mechanism Of Sh To Form Imentioning
confidence: 99%